PUBLIC SPEAKING KEPALA DESA DALAM MENINGKATKAN KEGIATAN GOTONG ROYONG PADA KALANGAN MILENIAL DI DESA SENDA MUKTI - Prihatini, Lishapsari; Noverin, Ririn (Lembaga Penelitian dan Pengabdian Masyarakat STISIPOL Candradimuka Palembang, 2019)
The importance of public speaking soft skills for village officials and village heads is the basis for the preparation of this Community Partnership Program (PKM). The focus of this service activity is to improve the ability to speak in public (public speaking). The specific purpose of this PKM is to encourage increased mutual cooperation activities among millennials in Senda Mukti Village, Pulau Rimau District, Banyuasin Regency, South Sumatra Province. Some of the methods used in this Community Partnership Program (PKM) are the question and answer method and discussion to identify knowledge and supporting technology. The lecture method is used during the learning process. In this service activity, the applied theory can provide the expected results. This can be seen from the increasing ability of most of the participants. Furthermore, participants are expected to be more confident in showing their public speaking skills to encourage millennials to be involved in community cooperation